FAKTOR-FAKTOR YANG MEMPENGARUHI PENGGUNAAN GENERALIZED AUDIT SOFTWARE DI KAP - Yenni, Elsa Imelda (Jurnal Paradigma Akuntansi, 2020)
The purpose of this study is to obtain empirical evidence about the Generalized Audit Software feature moderate the relationship between perceived ease of use and the use of Generalized Audit Software on external auditors in the Public Accountant Office for the period  2019.  The  research  sample  was  obtained  using  the  random  purposive  sampling method, namely 12 Offices Public Accountant. The model used in this study is a structural equation model and the data in this study were processed using SmartPLS version 3.0 for Windows. The results of this study indicate that perceived ease of use has no significant effect on the use of Generalized Audit Software, the complexity of Generalized Audit Software features  has  a  significant  effect  on  the  use  of  Generalized  Audit  Software  while  the complexity of Generalized Audit Software features does not moderate the relationship of perceived ease of use and the use of Generalized Audit Software.